LAYANAN KONSELING INDIVIDUAL DENGAN MENGGUNAKAN PENDEKATAN BEHAVIOR DALAM MENGATASI PESERTA DIDIK TERISOLIR (Studi Kasus Di Kelas VIII SMP Negeri 18 Kota Pontianak) - Devina; Halida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to identify and conduct an in-depth analysis of social isolation among eighth-grade students at SMP Negeri 18 in Pontianak. The subjects of this study are two eighth-grade students experiencing social isolation. This study employs a descriptive method with a qualitative approach in the form of a case study. The data collection techniques used were observation, interviews, and documentation. Meanwhile, the data analysis technique followed the steps of a case study, which include problem identification, diagnosis, prognosis, treatment, evaluation, and follow-up. In providing treatment for Case Subjects I and II, the researcher applied an individual counseling service model using a behavioral approach, incorporating assertiveness training and role-playing. Based on the research results, the isolated causal factors were internal factors in Case Subject I, such as emotional barriers, low self-confidence, social withdrawal, and a loss of interest in joining social groups. Meanwhile, internal factors in Case Subject II included being shy, quiet, lacking self-confidence, and withdrawing from the social environment. External factors included the family environment and the school environment. There were noticeable changes in Case I and Case II subjects after receiving treatment over four sessions. The changes observed in Case Subject I include being more willing to express frustration regarding things they dislike and showing greater confidence when asked by the teacher to present in front of the class. Meanwhile, the changes observed in Case Subject II include showing confidence when asked to come to the front of the class, no longer being quiet and withdrawn, being accepted by classmates, and being able to express thoughts and feelings to others.